2012
DOI: 10.1002/emmm.201201410
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT 6 receptor recruitment of mTOR as a mechanism for perturbed cognition in schizophrenia

Abstract: Cognitive deficits in schizophrenia severely compromise quality of life and are poorly controlled by current antipsychotics. While 5-HT6 receptor blockade holds special promise, molecular substrates underlying their control of cognition remain unclear. Using a proteomic strategy, we show that 5-HT6 receptors physically interact with several proteins of the mammalian target of rapamycin (mTOR) pathway, including mTOR. Further, 5-HT6 receptor activation increased mTOR signalling in rodent prefrontal cortex (PFC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(190 citation statements)
references
References 41 publications
(71 reference statements)
7
172
0
7
Order By: Relevance
“…Our previous studies of the 5-HT 6 receptor interactome identified neurofibromin as a candidate receptor partner (12). Immunoprecipitation followed by Western blot analysis confirmed the interaction of endogenously expressed neurofibromin with human (HA)-tagged 5-HT 6 receptor expressed in neuroblastoma-glioma NG108-15 cells (Fig.…”
Section: -Htsupporting
confidence: 59%
See 2 more Smart Citations
“…Our previous studies of the 5-HT 6 receptor interactome identified neurofibromin as a candidate receptor partner (12). Immunoprecipitation followed by Western blot analysis confirmed the interaction of endogenously expressed neurofibromin with human (HA)-tagged 5-HT 6 receptor expressed in neuroblastoma-glioma NG108-15 cells (Fig.…”
Section: -Htsupporting
confidence: 59%
“…In addition to its coupling to G proteins, the 5-HT 6 receptor interacts with the Src family tyrosine kinase Fyn (9), the Jun activation domain-binding protein 1 (10), and the microtubule-associated protein Map1b (11). The 5-HT 6 receptor also recruits the mammalian Target of Rapamycin (mTOR) Complex 1, and receptor-operated activation of mTOR signaling in prefrontal cortex (PFC) mediates its deleterious influence on cognition (12). Furthermore, 5-HT 6 receptors associate with and activate Cyclin-dependent kinase 5 (Cdk5) in an agonist-independent manner through mechanisms involving receptor phosphorylation by associated Cdk5 to promote migration of neurons and neurite growth (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The 5-HT 6 R belongs to the G-protein coupled receptor (GPCR) superfamily, and it stimulates adenylyl cyclase via Gs as well as extracellular-regulated kinase (ERK) signaling via the Srcfamily tyrosine kinase Fyn. Furthermore, 5-HT 6 R activates mTOR Complex 1 (mTORC1) in the prefrontal cortex, which is related to cognitive deficits, 2 and the receptor constitutively activates Cdk5 to control cortical neurons migration and promote neurite growth. 3 Blockade of 5-HT 6 R enhances cognitive performance in a broad range of tasks in rodents, 4,5 and phase II clinical studies have demonstrated efficacy of 5-HT 6 R antagonists (Iladopirdine = LuAE58054, SB742457, and AVN-211, Figure 1) in conjunction with donepezil in mild-to-moderate AD patients.…”
Section: T He Most Devastating Neurodegenerative Form Of Dementia Ismentioning
confidence: 99%
“…mTOR inhibitors were clinically approved to reduce restenosis after angioplasty for patients with vascular occlusion 63, 64. It has been reported that 5‐HT activated mTOR and p70S6K in neurons 65, 66. In the pulmonary artery, activation of p70S6K by 5‐HT induces SMC proliferation 67.…”
Section: Discussionmentioning
confidence: 99%